Liberia : Interim Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
Liberia's Interim Poverty Reduction Strategy (iPRS) sets out the emerging process and framework for recovery and reconstruction in the context of post-conflict Liberia. The iPRSP sets out the national socio-economic context, the preparatory process, dimensions of the emerging policy, capacity-building and program choices and priorities for poverty reduction and development, as well as anticipated implementation challenges. It also represents a further opportunity for deepening Liberia's development partnership. Liberia needs to be rebuilt at all levels of the public sector, private sector, and civil society.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet